Dalagang bukid Cultural Center of the Philippines. - Dela Rama, Honorata "Atang".; Ignacio, Leon.; Ilagan, Hermogenes; Manikan-Gomez, Noemi Angelita; Patag, Cynthia; Veloso, Lou.; Viray, Gamaliel; Molina, Pablo; Cultural Center of the Philippines; Tanghalang Pilipino Production ([Pasay City Cultural Center of the Philippines [Sentrong Pangkultura ng Pilipinas], 2002)
In the rush to modernize and develop, third world countries have sometimes lost their cultural bearings, forgetting their traditional art forms, and favoring instead newer, more "international", more Western influences. Because of this, some traditional forms have been lost; many are dying from neglect. The Cultural Center of the Philippines, with this project of recording on video disc the principal Philippine sarswelas seeks not only to preserve this traditional art form widely patronized in the pre-war years, but also to revive and popularize it. Showcasing the most important sarswelas produced in the different Philippine languages in the 20th century,this series hopes to define Filipino achievement in this genre and Filipino identity as distilled by this form. Most of all, through this series the CCP encourages contemporary theartre artists to revitalize the musical and develop it into a truly national dramatic form.
DVD.
Conductor, Francisco F. Feliciano ; Narrator, Noemi Manikan-Gomez.
Recording cast, Johanna Cabili (Angelita), Pablo Mariano Molino (Cipriano), Andrew Fernando (Don Silvestre), Margarita Gomez (Kobang), Leodigario del Rosario (Paco), Ma. Camila Lopez (Maria), Eduardo Briones (Sabas), Eduardo Briones (Parlong), Ma. Rachelle Gerodias (Petra), Arsenio Luna II (Tano), UP Singing Ambassadors.
Keywords: Reyna ng Kundiman -- 1979.